Performance Evaluation of Public Health Laboratories in Kenya - Lehmann, Joel; Muture, Bernard; Matu, Martin; Schneidman, Miriam (World Bank, Washington, DC, 2018)
This paper presents findings from a performance evaluation of laboratories in Kenya supported under the East Africa Public Health Laboratory Networking Project (EAPHLNP). The aim of the evaluation was to document progress and lessons learned, to enhance performance and foster sustainability.